Sensitivity of the Wisconsin Card Sorting Test (64-Card Version) versus the Tower of London (Drexel Version) for detecting executive dysfunction in children with epilepsy. Issue 3 (3rd April 2018) - MacAllister, William S.; Maiman, Moshe; Marsh, Megan; Whitman, Lindsay; Vasserman, Marsha; Cohen, Robyn J; Salinas, Christine M.
ABSTRACT: Executive function deficits are common in children and adolescents with epilepsy. Though the Wisconsin Card Sorting Task (WCST) is often considered the "gold standard" for executive function assessment, its sensitivity—particularly in the case of the 64-card version (WCST-64)—is insufficiently established in pediatric samples, including children and adolescents with epilepsy. The present investigation assesses the sensitivity of the WCST-64 in children and adolescents with epilepsy in comparison to another measure: the Tower of London – Drexel Version (TOL-DX). A total of 88 consecutively referred children and adolescents with epilepsy were administered both the WCST-64 and TOL-DX as part of a comprehensive neuropsychological evaluation. The sensitivity of WCST-64 and TOL-DX variables were established and relations with epilepsy severity measures and other executive function measures were assessed. Of the WCST-64 variables, Perseverative Responses is the most sensitive, but detected executive function impairment in only 19% of this clinically referred sample; in contrast, the TOL-DX Rule Violations detected executive function impairment in half of the sample. Further, TOL-DX performances are more strongly related to epilepsy severity variables and other executive function measures in comparison to the WCST-64. Despite its popularity amongst clinicians, the WCST-64 is not as sensitive to executive dysfunction in comparison to other measures of comparable administration time, such as the TOL-DX.